THE INFLUENCE OF DIGITAL CONTENT AND ONLINE REVIEWS ON THE PURCHASE DECISION OF GENERATION Z CONSUMERS AT KEDAI SEMOGA SUKSES SURABAYA - Tegar Fajar Ramadhan Makatita; Maharani Ikaningtyas (SYNTIFIC, 2026)
Background. The rapid development of digital technology has fundamentally altered consumer behavior, particularly among Generation Z, a cohort recognized as digital natives. In the food and beverage industry, business owners are increasingly required to leverage digital media to maintain competitiveness through effective management of digital content and online reviews. In this study, digital content and online reviews serve as independent variables, while purchase decision serves as the dependent variable. Research purpose. This study aims to analyze the simultaneous and partial influence of digital content and online reviews on the purchase decision of Generation Z consumers at Kedai Semoga Sukses Surabaya. Research method. A quantitative approach was employed using purposive sampling of 155 Generation Z respondents. Data were collected via questionnaire and analyzed using multiple linear regression with IBM SPSS Statistics. Findings. The results indicate that (1) digital content and online reviews simultaneously exert a positive and significant influence on purchase decisions (F=62.402; Sig.<0.001; R²=0.451); (2) digital content partially exerts a positive and significant influence (t=5.585; ?=0.307; Sig.<0.001); and (3) online reviews partially exert a positive and significant influence and constitute the most dominant variable (t=6.490; ?=0.435; Sig.<0.001). Both variables collectively explain 45.1% of the variation in Generation Z consumer purchase decisions. Conclusion. Online reviews proved to be more dominant than digital content, indicating that social validation from other consumers carries greater weight than information directly provided by the business.